Contribution of Arm Length, Arm Muscle Strength, and Leg Strength to Freestyle Swimming Ability - Hakim, Hikmad; Amahoru, Nurul Musfira; Awaluddin, Awaluddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine: 1) whether there is a contribution of arm's length to freestyle swimming ability; 2) whether is there a contribution of arm muscle strength to freestyle swimming ability; 3) whether is there a contribution of leg muscle strength to freestyle swimming ability and 4) is there a contribution of arm's length, arm muscle strength, and leg muscle strength to freestyle swimming ability. The population in this study were all Garuda Laut Makassar City athletes, specifically men, with a sample size of 30 athletes. The data analysis techniques used are descriptive, data normality tests, and correlation and regression analysis using the SPSS application. Based on the results of data analysis, this study concluded that: (1) Arm length contributed 31.2% to freestyle swimming ability, 2) Arm muscle strength contributed 44.2% to freestyle swimming ability, 3) Leg muscle strength contributes to freestyle swimming ability by 50.2%, and 4) Arm length, arm muscle strength, and leg muscle strength contribute to freestyle swimming ability by 59.5%.